The Present State and Tendencies of Housework (Part 2): The Housework related to Food Life - OOMORI, Kazuko; ITOH, Setsu; MIYAZAKI, Eiko; OOTAKE, Midori; AMANO, Hiroko; ABE, Kazuko; KATOH, Etsu; YOSHIMOTO, Teruko (Journal of Home Economics of Japan, 1978)
The style of the Japanese food life have been changing since 1955. Problems of the housework are faced with the changes. 1. When the wives get dinner ready, it takes from one hour to 11/2 hours for meal preparation. 61.9% of families show that all family members are completely together at dinner time. 2. The wives do the housework of the food life without any help by other family members. The way of thinking that each member of family should learn housework of food life was hardly found. 3. New problems of the housework exist with the increase in the consumption of ready-made foods. 4. In the future, it is the subject for us to research on the socialization of the housework in the food life and rationalization of the housework in each home.